Hoax and Morals in Al-Quran and Hadith - Ilham Fajar; Mujiyo Mujiyo (Gunung Djati Conference Series, 2021)
This study aims to discuss morality in the Quran and Hadith related to hoax. The method used is a qualitative type through library research with content analysis. The discussion includes worldview on hoax, the Quran and Hadith view point, and moral analysis in the Quran and Hadith related to hoax. This study concludes that a hoax is all things manipulated from a person what they really deserve. Some morals that can be done dealing with hoax according to the Quran and Hadith view point, both, are in the form of prevention and countermeasures, including saying the truth, having good prejudice, and doing clarification.